Probiotic induced synthesis of microbiota polyamine as a nutraceutical for metabolic syndrome and obesity-related type 2 diabetes - Bui, Tina I.; Britt, Emily A.; Muthukrishnan, Gowrishankar; Gill, Steven R. (Frontiers in Endocrinology, 2023)
The gut microbiota regulates multiple facets of host metabolism and immunity through the production of signaling metabolites, such as polyamines which are small organic compounds that are essential to host cell growth and lymphocyte activation. Polyamines are most abundant in the intestinal lumen, where their synthesis by the gut microbiota is influenced by microbiome composition and host diet. Disruption of the host gut microbiome in metabolic syndrome and obesity-related type 2 diabetes (obesity/T2D) results in potential dysregulation of polyamine synthesis. A growing body of evidence suggests that restoration of the dysbiotic gut microbiota and polyamine synthesis is effective in ameliorating metabolic syndrome and strengthening the impaired immune responses of obesity/T2D. In this review, we discuss existing studies on gut microbiome determinants of polyamine synthesis, polyamine production in obesity/T2D, and evidence that demonstrates the potential of polyamines as a nutraceutical in obesity/T2D hosts.